Margens em construção: um panorama dos undergrounds e do faça-você-mesmo no Brasil (2016 – 2018) - Marques, Victor Otávio Carvalho (2020)
The presente research aim to explore a panorama of underground music scenes from Brazil between the years of 2016 and 2018. Its objective was the observation of the way those spaces, on the borders of culture, develop and establish itself in our contemporaneity, mostly in relationship with a variety of medias that those processes take to itself. Focus those movements is something of major importance because its existence regardless of external agents, it takes form by na ensemble of practices of doit-yourself, in other words, the necessary crafitness for its existence come from the same people that compose it. As a mainly hypothesis, we observe that, in its own way, those cultural processes search in different medias the ways to be materialized, dysfunctionalizing it in its comercial precepts. Those peripheral spaces become coextensives to different regions and cities, creating collectivities that are constantly moving.For the development of these starting points, we started to follow and in another cities of Brazil with the purpose to observe the processes in action. Besides that, we lean on reflections of authors such like Jerusa Pires Ferreria, Paul Zumthor, Iuri Lótiman, Mikhail Bakhtin, and also other members of Russian school of semiotics and the formalists, Giorgio Agamben, Michel de Certeau, Octavio Paz and other that composes the theoretical foundation of this thesis. The conclusion of the research points to a mismatch between the already consolidate productions of rock and the undergrounds that were created by and in spite of them. It is noted that rock‟n roll that moved crowds in the past wanders on the end of its existence as an alive semiotic process, opening space to the undergrounds, each time more actives and permissive